Marketing Mix and Purchase Decisions on the Shopee Marketplace in Makassar City - Atiqah, Zahirah Urjuwani; Yamin, Muh Nur; Syarifuddin, Syarifuddin (Pinisi Business Administration Review, 2024)
Marketing Mix and Purchase Decisions on the Shopee Marketplace. Business Administration Study Program. Supervised by Muh. Nur Yamin and Maya Kasmita.. This study aims to determine the marketing mix and purchasing decisions on the shopee marketplace in Makassar City. This research uses Quantitative research type. Data collection techniques carried out are primary data (Questionnaire, Observation, and Documentation). The sample used was a sample formulated using the Slovin formula, as many as 100 respondents. Data is obtained from research results that are processed using data analysis. The results of the study show that the regression coefficient of 1.329 means that the marketing mix has a positive effect on purchases at the shopee marketplace in Makassar City. This shows that with the marketing mix, there is an increase in purchases on the shopee marketplace and vice versa if there is no marketing mix, the increase in purchases on the shopee marketplace will not increase. The value of the coefficient of determination is obtained at 0.626 or 62.6% which means that the influence of Marketing Mix (X) on Purchasing Decisions (Y) is in the High or Strong category (assuming that other factors are constant).